Impact of both early-age acclimation and linseed dietary inclusion on fat deposition and fatty acids’ meat traits in heat-stressed broiler chickens - Zineb, Bengharbi; Said, Dahmouni; Djilali, Benabdelmoumene (Journal of Advanced Veterinary and Animal Research, 2021)
Objective: The purpose of this work was to investigate the combination of early-age acclimation and linseed dietary inclusion in enriching polyunsaturated fatty acids (PUFAs) in broilers’ meat as a strategy to mitigate heat stress. Materials and Methods: A total of 400 broiler chicks were assigned to four experimental groups with four duplicates (25 animals each): C: control (basal diet), AC: early-age acclimated (basal diet), Cl: fed 5% ground linseed, and Acl: early-age acclimated and fed 5% ground linseed. The lipid and fatty acid contents of different parts (breast, thigh, liver, subcutaneous, and abdominal fat) of broilers were determined. Results: Low levels of lipids and unsaturated fatty acids have been found in the meat of acclimated broilers. Higher levels of linolenic acids were noted in Cl thigh meat compared to C (6% vs. 2.68%, respectively). The results showed that oleic and linoleic acids constitute a large part of the PUFAs of different meats. The most elevated levels of monounsaturated fatty acids were recorded in the breast meat of AcL animals. The highest content of omega-3 was recorded in the liver of AcL animals compared to that of C (14.98% vs. 7.8%, respectively). Conclusion: We suggest that the combination of treatments during hot conditions has led to the reversion of the environment-affected variables to accepted values, and yields better thermoresistance, PUFA-enriched meat, and safeguard animal health which conferred to birds’ better solutions to reduce fatigue and hypoxic activities, which induces a considerable consumption of oxygen. J. Adv. Vet. Anim. Res., 8(2): 237-245, June 2021